Linking organizational trust and performance through ambidexterity (2019)
Purpose – The literature provides mixed empirical evidence on the trust–performance relationship. The purpose of this paper is to shed additional light on this relationship, using organizational ambidexterity as an explanatory variable. Design/methodology/approach – A structural equation technique was used to examine survey data obtained from 377 Spanish organic agro-food industries. Findings – The results obtained provide support to show that organizational ambidexterity has a mediating role in the relationship between organizational trust and firm performance, in the organic agro-food industry. Research limitations/implications – This study used a sample taken from only one industry and country. Future research could expand the model to other countries and industries. Practical implications – This study suggests that managers could use tools to enhance organizational trust that would help to improve firm performance, given that trust can cause employees to adopt behaviors related to ambidexterity. Therefore, managers can use trust as a mechanism to encourage more stable relationships, increase the transfer of existing knowledge, facilitate experimentation and express ideas to promote organizational ambidexterity, thus benefiting firm performance. Originality/value – This research paper offers a new insight into how ambidexterity affects the organizational trust-firm performance relationship. Even though there is growing theoretical importance given to the concepts of trust and ambidexterity, the empirical evidence that demonstrates how both variables are related to firm performance, especially in emerging sectors, is scarce.